Does Informal Care from Adult Children Reduce Nursing Home Admissions for the Elderly? - Anthony T. Lo Sasso; Richard W. Johnson (SAGE Publishing, 2002)
Despite the policy importance, particularly as society ages, little is known about the impact of informal care on nursing home admissions. This paper jointly models the receipt of regular help from adult children and subsequent nursing home care, using data from the Study of Asset and Health Dynamics Among the Oldest Old (AHEAD). Results indicate that frequent help from children with basic personal care reduces the likelihood of nursing home use over a subsequent two-year period by about 60% for disabled Americans age 70 and older. However, we found no significant reduction in nursing home admissions when help was measured more broadly to include assistance with chores and errands.